2015
DOI: 10.1093/ecco-jcc/jjv130
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Earlier Anti-TNF Treatment on IBD Disease Complications?

Abstract: This study was unable to confirm a benefit of earlier anti-TNF treatment on IBD disease complications. This could be explained by more aggressive treatment earlier in disease, resulting in fewer IBD complications. However, it seems more likely that inappropriate selection of patients for therapy leads to suboptimal treatment and subsequently suboptimal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
1
25
2
Order By: Relevance
“…Recently, data from the Swiss Cohort showed that early treatment was associated with reduced risk of bowel strictures (p<0.05), intestinal surgery (HR 0.322, p=0.005), perianal surgery (HR 0.361, p=0.042) and development of any complication (HR 0.567, p=0.006)38 One study on 168 newly diagnosed patients with CD in South Korea39 showed that early use of thiopurines (within 6 months of diagnosis) was associated with higher rates of clinical and steroid-free remission (p=0.043 and p=0.035, respectively). Similar data were found in the DELTA Cohort between patients starting anti-TNF within 16 months since diagnosis and those receiving the first anti-TNF later 40. The CONNECT study from South Korea,41 instead, showed that early use of thiopurines (median time 1.5±1.9 months since diagnosis) was associated with lower rates of CD-related surgery (24.1 vs 36.4%; p<0.001) and longer time to surgery (12 vs 9 months, p=0.017) than in patients treated with a conventional step-up approach.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Recently, data from the Swiss Cohort showed that early treatment was associated with reduced risk of bowel strictures (p<0.05), intestinal surgery (HR 0.322, p=0.005), perianal surgery (HR 0.361, p=0.042) and development of any complication (HR 0.567, p=0.006)38 One study on 168 newly diagnosed patients with CD in South Korea39 showed that early use of thiopurines (within 6 months of diagnosis) was associated with higher rates of clinical and steroid-free remission (p=0.043 and p=0.035, respectively). Similar data were found in the DELTA Cohort between patients starting anti-TNF within 16 months since diagnosis and those receiving the first anti-TNF later 40. The CONNECT study from South Korea,41 instead, showed that early use of thiopurines (median time 1.5±1.9 months since diagnosis) was associated with lower rates of CD-related surgery (24.1 vs 36.4%; p<0.001) and longer time to surgery (12 vs 9 months, p=0.017) than in patients treated with a conventional step-up approach.…”
Section: Introductionsupporting
confidence: 79%
“…Recently, Nuij  et al 40 found no differences in terms of inflammatory bowel disease (IBD)-related complications and mucosal healing in the Delta cohort, evaluating patients treated with anti-TNF within 16 months from diagnosis (57% of the total study population) compared with those receiving anti-TNF later. Additionally, no significant difference was shown when more stringent criteria of 12 months since diagnosis were applied.…”
Section: Introductionmentioning
confidence: 99%
“…But there are also conflicting results regarding this topic; in a recent population-based cohort study on 413 IBD patients, overall, one-third of newly diagnosed IBD patients in the cohort experienced an IBD-related complication in the first few years after diagnosis (one-fifth had extraintestinal manifestations, 13% had fistulae or abscesses, and 14% required surgery). The study did not demonstrate a beneficial effect of starting anti-TNF agents early compared to starting anti-TNF agents late with respect to the occurrence of disease complications, mucosal healing, and surgery [43] .…”
Section: Discussionmentioning
confidence: 58%
“…A Dutch population-based cohort study (85 IBD patients: 66 with CD, 16 with UC, 3 with unclassified IBD) could not show a benefit of early anti-TNF treatment as opposed to late (more than 16 months after diagnosis) anti-TNF treatment on the amount of IBD-related disease complications [23]. Earlier anti-TNF treatment did not lead to more mucosal healing.…”
Section: Introductionmentioning
confidence: 92%
“…This could be assigned given that in this cohort, treatment strategies differed from earlier studies, with patients being treated more aggressively early on, resulting in less development of IBD complications and a population too homogeneous to detect differences in outcome. However, it is also possible that inappropriate selection of patients for a specific therapy led to a suboptimal drug efficacy, lacking the ability to modify the natural course of the disease and prevent the development of disease complications [23]. In the Swiss IBD cohort, treatment with immunomodulators or TNF antagonists within the first 2 years after CD diagnosis was associated with reduced risk of developing bowel strictures [24].…”
Section: Introductionmentioning
confidence: 99%